Processing of experimental data of the process of refining nuclear material Zr1% Nb by electron-beam melting by means of interval analysis methods - Yefimov, A. V.; Pylypenko, M. M.; Potanina, T. V.; Yesypenko, T. A.; Harkusha, T. A.; Stadnik, Yu. S. (Kharkov Institute of Physics and Technology, 2019)
The possibilities of applying the methods and models of interval analysis, which take into account the uncertainties in the specification of data for Zr1%Nb alloys, to more accurately determine the relationship between the microhardness of Zr1%Nb alloy samples and the content of oxygen in them, have been investigated. The correctness of the application of methods and models of interval analysis for processing the results of experiments to study the properties of nuclear materials is shown.

Досліджено можливості застосування методів і моделей інтервального аналізу, що враховують невизначеності в заданні даних для сплавів Zr1%Nb, для більш точного визначення взаємозв'язку між мікротвердістю зразків сплаву Zr1%Nb та процентним вмістом кисню в них. Показана коректність застосування методів і моделей інтервального аналізу для обробки результатів експериментів з вивчення властивостей ядерних матеріалів.
Обробка експериментальних даних процесу рафінування ядерного матеріалу Zr1% Nb електронно-променевою плавкою методами інтервального аналізу
Keywords: interval analysis; microhardness; nuclear materials; alloys; chemical reactions; інтервальний аналіз; мікротвердість; ядерні матеріали; сплави; хімічні реакції